Large-scale preparation of heterometallic chalcogenide MnSb2S4 monolayer nanosheets with a high visible-light photocatalytic activity for H2 evolution. Issue 91 (27th October 2016) - Lin, Zheguan; Ning, Shangbo; Yang, Zhenya; Zhang, Zizhong; Huang, Shuping; Long, Jinlin; Lin, Huaxiang; Wang, Xuxu
Abstract : Monolayered 2D MnSb2 S4 nanosheets with a sandwich substructure of [SbS] + –[MnS2 ] 2− –[SbS] + improve charge separation and photocatalytic H2 evolution activity. Abstract : Free standing MnSb2 S4 2D monolayer nanosheets were developed by a simple calcination of the neutral hydrazine molecule bridged chalcogenide, and were found to display a highly efficient and stable activity for photocatalytic hydrogen evolution from water under visible light irradiation (420–730 nm).